2016
DOI: 10.1002/elan.201600099
|View full text |Cite
|
Sign up to set email alerts
|

The New Application of Boron Doped Diamond Electrode Modified with Nafion and Lead Films for Simultaneous Voltammetric Determination of Dopamine and Paracetamol

Abstract: A new voltammetric procedure for the simultaneous determination of dopamine (DA) and paracetamol (PA) using boron doped diamond electrode modified with Nafion and lead films (PbF/Nafion/BDDE) was investigated. The use of this electrode resolved the overlapped voltammetric waves of DA and PA into well‐defined peaks with peak to peak separation of about 320 mV. Under the optimized experimental conditions in differential pulse voltammetric technique, DA and PA gave a linear response over the ranges 2.0×10−7–1.0×1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…In addition to the above illustrated carbon-based electrodes, some research studies reported other carbon-based electrodes such as boron-doped diamond electrodes (BDDE) [ [125] , [126] , [127] , [128] ] and carbon-ceramic electrodes (CCE) [ [129] , [130] , [131] , [132] , [133] , [134] ] as shown in Table 5 . Tyszczuk-Rotko et al.…”
Section: Other Types Of Carbon-based Electrodes For the Determination Of Pctmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the above illustrated carbon-based electrodes, some research studies reported other carbon-based electrodes such as boron-doped diamond electrodes (BDDE) [ [125] , [126] , [127] , [128] ] and carbon-ceramic electrodes (CCE) [ [129] , [130] , [131] , [132] , [133] , [134] ] as shown in Table 5 . Tyszczuk-Rotko et al.…”
Section: Other Types Of Carbon-based Electrodes For the Determination Of Pctmentioning
confidence: 99%
“… Working electrode Modifier Methods Linearity (μM) LOD (μM) Application/Recovery (%) Advantages Disadvantages Refs. BDDE Nf-Pb DPV 0.5–200 0.175 Tablet/100.04 B, C, D C, G [ 126 ] BDDE Nf-Pb DPV 0.5–1000 0.14 Human urine/102.5–104.67 Whole blood/103.44–105.58 Serum/103.12–104.48 B, C, E G [ 127 ] BDDE Nf-Bi DPV 0.2–1000 0.0262 Tablet/105.14 A, B, C C, G [ 128 ] CCE SWCNT DPV 0.2–150 3 Tablet/98.79–101.51 PCT syrup/99.52–102.46 Human serum/101,103 B, C, E B, F [ 129 ] CCE SWCNT DPV 0.08–200.0 0.05 Tablets/97.23–101.7 PCT Syrup/98.3–104.6 Acifen/100.8–101.6 A, B, C, D F [ 130 ] CCE SWCNT DPV 0...…”
Section: Other Types Of Carbon-based Electrodes For the Determination Of Pctmentioning
confidence: 99%
See 1 more Smart Citation
“…Os eletrodos não modificados mais comuns são de pasta de carbono 9 , de carbono vítreo 10 e, principalmente, de diamante dopado com boro (DDB). Na literatura, há diversas metodologias referentes ao estudo da oxidação do paracetamol sobre DDB para determinações simultâneas com codeína 11 , ácido ascórbico 12 , nimesulida 13 , penicilina V 14 , dopamina 15 , ibuprofeno 16 , tramadol 17 , cafeína 18,19 e cafeína com propifenazona 20 , ibuprofeno 21 , orfenadrina 22 e aspirina 23 . Entretanto, até o momento não foram encontrados registros de metodologias validadas utilizando ferramentas estatísticas, bem como de estudos realizados em águas naturais.…”
Section: Figura 1 Fórmula Estrutural Do Fármaco Paracetamolunclassified